Lax Triples for Integrable Surfaces in Three-Dimensional Space - Jan L. Cieśliński; Artur Kobus (Advances in Mathematical Physics)
We study Lax triples (i.e., Lax representations consisting of three linear equations) associated with families of surfaces immersed in three-dimensional Euclidean space E3. We begin with a natural integrable deformation of the principal chiral model. Then, we show that all deformations linear in the spectral parameter λ are trivial unless we admit Lax representations in a larger space. We present an explicit example of triply orthogonal systems with Lax representation in the group Spin(6). Finally, the obtained results are interpreted in the context of the soliton surfaces approach.